Calculation and Minimisation of Garbage Bits in Quantum Reversible Circuits - Tanwar, Rajeev (My University, 2007)
Quantum Computation and Quantum Information is the study of information processing task that can be accomplished using Quantum mechanical systems. It is relatively new and emerging area in the field of computing that taught us to think physically about computation. This approach yields many new and exciting capabilities for information processing and communication. Quantum Computing will be a total change in how the computer will operate and function. The explorations in this field may one day result in information processing devices with capabilities far beyond today’s computing and communication systems. Reversible Computation is a fundamental aspect necessary for Quantum Computation. The overall advantage of making the computation reversible on a Classical Computer is that heat dissipation is reduced and new techniques like Quantum Computing can be approached with this foundational change in the way processing is done. Such combination of Classical and Quantum Computers would be indispensable, since our perception is classical. The primary objective of this thesis is to gain insight into the Reversible Computation and its use in Quantum Computing and to study Quantum Information Processing. However the main task that was identified to be pursued as a focal issue around which the concepts of Reversible and Quantum Computation were to be built is: Determining the function of increase in the number of “ancilla” bits and “garbage” bits in reversible computing in comparison with conventional performance with respect to the implementation of basic circuits. Also to find out how reversible circuit can be optimised in terms of number of gates, garbage bits and logical complexity.
Keywords: Garbage Bits in Quantum Reversible Circuit; Moore's Law; Fredkin Gate; Toffoli Gate